Does Lithium Deserve a Place in the Treatment Against COVID-19? A Preliminary Observational Study in Six Patients, Case Report - Spuch, Carlos; López-García, Marta; Rivera-Baltanás, Tania; Rodrígues-Amorím, Daniela; Olivares, José M. (Frontiers in Pharmacology, 2020)
Lithium has shown the capacity to: a) inhibit the replication of several types of viruses, some of them similar to SARS-CoV-2 virus, b) increase immune response reducing lymphopenia, and c) reduce inflammatory activity by preventing or reducing the cytokine storm. We have treated six patients with severe COVID-19 infection with lithium carbonate. We have found that this treatment significantly reduced the reactive C-Protein, increased lymphocyte levels and decreased the neutrophil-lymphocyte ratio, improving both inflammatory activity and immune response in these patients. We propose that lithium carbonate may deserve a place in the treatment against COVID-19.